Efektifitas Pemberian Kredit pada PT. BRI (Persero) Tbk Unit Jatinegara Binjai - Dito Aditia Darma Nasution; Galih Supraja Anisa; Annisa Fajariah Damanik (Journal of Business and Economics Research (JBE), 2022)
In lending, banks have used the 5C principle. However, the bank is still not optimal in implementing all the 5C principles. To achieve effective credit management, banks must make improvements in credit analysis. This type of research method is descriptive. This study was used to determine the credit distribution applied by PT. BRI (Persero) Tbk, includes: Credit Application Process, Credit Approval Process, Credit Supervision and Repayment Techniques, and Non-performing Loans Settlement. Financial ratio analysis is liquidity ratio including quick ratio, banking ratio (asset to loan ratio, cash ratio, loan to deposit ratio) and profitability ratio including gross profit margin, net profit margin, return on equity capital, and return on total assets. The research site chosen for the research location is PT. BRI (Persero) Tbk Unit Jatinegara Binjai. In this study, the data collection method used to collect the required data is documentation, namely data collection techniques by viewing and using company reports and records. The conclusion of the analysis is that the Cash Ratio is good, the Loan to Deposit Ratio (LDR) is good, the Return on Equity (ROE) is good, the Return on Assets (ROA) is good, and the quick ratio is not good.